2012
DOI: 10.1002/jwmg.369
|View full text |Cite
|
Sign up to set email alerts
|

Demography of greater prairie‐chickens: Regional variation in vital rates, sensitivity values, and population dynamics

Abstract: Intensification of rangeland management has coincided with population declines among obligate grassland species in the largest remaining tallgrass prairie in North America, although causes of declines remain unknown. We modeled population dynamics and conducted sensitivity analyses from demographic data collected for an obligate grassland bird that is an indicator species for tallgrass prairie, the greater prairie-chicken (Tympanuchus cupido), during a 4-year study in east-central Kansas, USA. We examined comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 70 publications
3
77
0
Order By: Relevance
“…Our results confirm the strong influence of vertical nesting cover on prairie-chicken nesting ecology (McNew et al, 2014), and explain variation in fecundity observed over gradients of rangeland management intensity (McNew et al, 2012a;Robbins et al, 2002).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results confirm the strong influence of vertical nesting cover on prairie-chicken nesting ecology (McNew et al, 2014), and explain variation in fecundity observed over gradients of rangeland management intensity (McNew et al, 2012a;Robbins et al, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…Prairie-chickens require a diverse mosaic of floristic and structural grassland habitats for successful reproduction and survival: open sites at relatively high elevations for display arenas or leks, dense vegetative cover for concealment during nesting, and intermediate vegetative structure rich in forbs for brood-rearing (Svedarsky et al, 2000;Johnson et al, 2011). Our recent research indicates that high predation on nests and young is the primary cause of population declines, and that predation risk is linked to a lack of adequate vegetative cover at prairie-chicken nest sites in the Flint Hills (McNew et al, 2012a(McNew et al, , 2014. However, the relationships between rangeland management practices, nesting cover, and prairie-chicken fecundity have not been evaluated.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 97%
“…Upland sandpiper populations could be buffered against poor nest survival because they lay replacement clutches, and annual survival is relatively high (*0.7, Sandercock, unpublished data). Nevertheless, current rangeland management could be reducing population viability of upland sandpipers and other grassland birds in the Flint Hills ecoregion McNew et al 2012; this study).…”
Section: Habitat-specific Demographymentioning
confidence: 95%
“…Avoidance of these landscape features may be related to patterns of habitat fragmentation. Fragmentation of native prairie by cropland and anthropogenic features such as roads, power lines, fences, and towers has been linked to elevated mortality rates and shifts in life-history strategies in Greater and Lesser Prairie-Chickens, leaving these populations more vulnerable to local extinction (Ryan et al 1998, Patten et al 2005, McNew et al 2012.…”
Section: Spatial Ecologymentioning
confidence: 99%
“…Prairie-chicken populations are declining in the core of their extant range in Kansas due to low rates of nest, brood, and adult survival, which are related to high rates of predation and intensification of land use for cattle production (McNew et al 2012, Pitman et al 2012. Prairie-chickens require a mosaic of habitat types for successful reproduction and survival: open sites at relatively high elevations for display arenas used for lekking, dense vegetative cover for concealment during nesting, and areas of intermediate vegetative structure that are rich in forbs for foraging and rearing of broods (Gregory et al 2011, Johnson et al 2011, Matthews et al 2013.…”
Section: Introductionmentioning
confidence: 99%